2002
DOI: 10.1056/nejmoa012750
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Oscillatory Ventilation versus Conventional Mechanical Ventilation for Very-Low-Birth-Weight Infants

Abstract: There was a small but significant benefit of high-frequency oscillatory ventilation in terms of the pulmonary outcome for very-low-birth-weight infants without an increase in the occurrence of other complications of premature birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(213 citation statements)
references
References 56 publications
7
199
1
6
Order By: Relevance
“…To avoid any interference of mechanical ventilation with these parameters, we stopped the oscillations during HFOV, making extubation a true transition from endotracheal to nasal CPAP. According to our local protocol, infants were extubated to a nasal CDP 2 cmH 2 O lower than during HFOV, because it has been suggested that the alveolar CDP delivered by the SensorMedics 3100 ventilator is 1-2 cmH 2 O lower than the pressure recorded at the hub of the endotracheal tube when delivered with an inspiratory time of 33%, as is custom in our unit (18)(19)(20). Despite this lower CDP EELV remained stable after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid any interference of mechanical ventilation with these parameters, we stopped the oscillations during HFOV, making extubation a true transition from endotracheal to nasal CPAP. According to our local protocol, infants were extubated to a nasal CDP 2 cmH 2 O lower than during HFOV, because it has been suggested that the alveolar CDP delivered by the SensorMedics 3100 ventilator is 1-2 cmH 2 O lower than the pressure recorded at the hub of the endotracheal tube when delivered with an inspiratory time of 33%, as is custom in our unit (18)(19)(20). Despite this lower CDP EELV remained stable after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies, published in the same journal and using similar methodologies, found differing results. 36 Courtney et al 37 compared HFOV with SIMV in infants of 600 to 1200 g birthweight and found a small reduction in the incidence of CLD. However, it is plausible that this difference might be more attributable to the use of SIMV in the control group, and that if A/C had been used, it might have even disappeared.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Porém, nas últimas 2 décadas, vários estudos clínicos têm sido realizados, e os resultados continuam controversos [57][58][59][60][61][62][63][64][65] . Duas revisões feitas pela Cochrane Database não evidenciaram grandes vantagens do uso da ventilação de alta freqüência.…”
Section: Ventilação De Alta Freqüênciaunclassified